Termites in the trading system - Bhagwati, Jagdish (Oxford University Press, 2008)
Jagdish Bhagwati, the internationally renowned economist who uniquely combines a reputation as the leading scholar of international trade with a substantial presence in public policy on the important issues of the day, shines here a critical light on Preferential Trade Agreements, revealing how the rapid spread of PTAs endangers the world trading system...